Development of Tar Removal Technologies for Biomass Gasification using the By-products. (August 2015) - Nakamura, Shunsuke; Siriwat, Unyaphan; Yoshikawa, Kunio; Kitano, Shigeru
Abstract: The technical obstacle of biomass gasification technology is the effective removal of tar, which will cause the clogging of pipes and engines. In this research, in order to develop the low-cost and high-efficiency tar removal technologies, the tar removal performances of bio-oil and char, which are the by-products of biomass gasification processes, were investigated. For this research, the scrubber with 100L of bio-oil and the char bed with 10 kg of char and 3 kg of activated carbon were prepared in the pilot-scale gasification plant. The results show that the bio-oil scrubber and the char bed were effective for tar removal and both of them removed about 60% of tar from the producer gas. It is noteworthy that the tar removal performance of the bio-oil scrubber did not decrease with the passage of time. This implies that the bio-oil scrubber had some big advantages, such as no cost for purchase and transportation of absorbent and no need to change the absorbent inside the scrubber.